Rake. Series 5 [videorecording (DVD)] - Duncan, Peter, 1964-; Knight, Andrew, 1953-; Roxburgh, Richard; Day, Matt, 1971-; Pickering, Adrienne, 1981-; Brazier, Caroline (Actor); Box, Kate; Joyce, Keegan; Garvey, Damien; LaPaglia, Anthony (Acorn/RLJ Entertainment, 2019)
The final season tackles the contentious world of politics, with disbarred lawyer Cleaver Greene having won an Australian Senate seat on a campaign promise to do nothing. But even Cleaver's low expectations fall short, as he contends with a right-wing nemesis, a noxious gas attack believed to be the work of terrorists, and a disastrous visit from the US defense secretary. Can Cleaver outmaneuver his cutthroat colleagues, or will his self-destructive behavior destroy his budding new career?